INFLUENCE OF MATERIAL HARDNESS AND PARTICLE VELOCITY ON EROSIVE WEAR RATE - Kosa, Ergin; Göksenli, Ali (Journal of Mechanical Engineering, 2018)
Many parameters such as medium conditions and material properties are effective on erosiveabrasive wear rate. In this study, effect of particle impact velocity and hardness of material on wear rate and wear mechanism was investigated. All tests were carried out in 20% sand-water mixture. Impact velocities of the particles were ranking between 2.04 m/s and 4.76 m/s. Hardness values of St 37 and Ck 45 steels were changed by applying different heat treatments. After wear tests it was concluded that by an increase of impact velocity and decrease of material hardness, wear rate increased. This increase was by soft materials more dominant than by hard materials. After morphological investigations it is concluded that by an increase of material hardness, number and size of craters on the surface after erosion tests decreased. By using experimental test results, a new mathematical formulation was developed to emphasize the relation between impact velocity and material hardness on wear rate.